2001
DOI: 10.1038/oby.2001.107
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction and Binge Eating in Obese Women: The Role of Restraint and Depression

Abstract: WARDLE, JANE, JO WALLER, AND LORNA RAPOPORT. Body dissatisfaction and binge eating in obese women: the role of restraint and depression. Obes Res. 2001;9:778 -787. Objective: This study examined the association between body dissatisfaction and binge eating, and the mediating role of restraint and depression among obese women. Research Methods and Procedures: Participants were obese women taking part in a cognitive-behavioral treatment program who completed self-report measures at baseline (n ϭ 89) and post-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 52 publications
8
52
1
5
Order By: Relevance
“…All EDE-Q subscale scores were higher in the obese subgroup and all correlated strongly within the obese subgroup to psychological distress. This confirms previous studies that have shown dieting, weight and shape concerns or body image problems, eating concerns and binge eating to be high in obese people 8,15,18,24,38,39 and those that indicate a relationship with these factors with psychological health. 8,15,18,24 Although the presence of ED psychopathology increased psychological distress in all women irrespective of weight status, this study indicates that the levels of ED psychopathology are much higher in women with obesity, and therefore an important factor contributing to the poor health of this population group.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…All EDE-Q subscale scores were higher in the obese subgroup and all correlated strongly within the obese subgroup to psychological distress. This confirms previous studies that have shown dieting, weight and shape concerns or body image problems, eating concerns and binge eating to be high in obese people 8,15,18,24,38,39 and those that indicate a relationship with these factors with psychological health. 8,15,18,24 Although the presence of ED psychopathology increased psychological distress in all women irrespective of weight status, this study indicates that the levels of ED psychopathology are much higher in women with obesity, and therefore an important factor contributing to the poor health of this population group.…”
Section: Discussionsupporting
confidence: 79%
“…This confirms previous studies that have shown dieting, weight and shape concerns or body image problems, eating concerns and binge eating to be high in obese people 8,15,18,24,38,39 and those that indicate a relationship with these factors with psychological health. 8,15,18,24 Although the presence of ED psychopathology increased psychological distress in all women irrespective of weight status, this study indicates that the levels of ED psychopathology are much higher in women with obesity, and therefore an important factor contributing to the poor health of this population group. Furthermore this study indicates that among women with obesity, disordered cognitions and high concerns with eating, weight and shape and dietary restraint play a significant role in predicting psychological distress (rather then other ED behaviours which play a greater role in other women) and thus these particular ED features may possibly be important to target in obesity treatment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…O pressuposto inicial foi que o foco prematuro na questão do emagrecimento poderia incentivar um aumento da restrição alimentar e que esta seria um fator predisponente para a ocorrência da compulsão alimentar. À medida que o perfil dos pacientes com TCAP foi sendo estudado, observou-se que, embora a restrição alimentar possa favorecer a ocorrência de compulsão em alguns pacientes, esse efeito não é observado em todos os casos 5,41 . Esse fato pode ser exemplificado pelos resultados obtidos nos estudos que associam TC com dietas que incentivam a restrição alimentar.…”
Section: Discussionunclassified
“…Em alguns ensaios clínicos, a diminuição do grau de insatisfação com a forma corporal ocorreu mesmo na ausência de perda de peso 8,22,30 . Estudos de TCC com obesos sem TCAP 41,42 também revelaram que a melhora da insatisfação com a imagem corporal não estava correlacionada com o IMC. Esses achados levaram Wolff & Clark 22 e Parham 43 a sugerirem que o grau de satisfação com a imagem corporal pode estar mais correlacionado com o sistema de crenças do indivíduo do que com o grau de obesidade, ressaltando a importância de incluir estratégias para modificação do sistema de crenças nos programas de tratamento, objetivando melhorar a relação do paciente com sua imagem corporal.…”
Section: Atitudes Associadas à Alimentação E à Forma Corporalunclassified